Comparison Study of Halal Management System in Indonesia and Malaysia - Yustianingsih, Lidia; Mufid, Ali; Maifiah, Mohd Hafidz Mahamad; Gunawan, Setiyo (Halal Center ITS, 2024)
Halal standards between countries were varied, potentially leading to differences in halal product status decisions. In developing global halal standards, Indonesian and Malaysian halal standards were often used as references. This research aimed to gain a deeper understanding of the halal management systems in Indonesia and Malaysia in order to identify differences and similarities in halal regulations and management, including animal slaughtering practices. The halal management systems in Indonesia and Malaysia are mainly comparable. Some non-conforming differences include the certification procedure, certificate validity period, the halal products category, and the number of internal halal committees. Some essential differences are the halal certificate compulsoriness, stunning regulation, and the product name, brand, or synonym considered to be halal. The additional procedure used after slaughter, thoracic sticking, has become an emerging issue in developing a Mutual Recognition Agreement (MRA) of halal certificates for domestic products between Indonesia and Malaysia.